Aspek Sosial dalam Novel “33 Senja Di Halmahera” Karya Andaru Intan - Afni Nurul Ikhsan; Bambang Sumadyo (Universitas Indraprasta PGRI, 2021)
The aims of this research are 1) to describe the economy of the Halmahera community in Andaru Intan's 33 Senja di Halmahera novel, 2) to describe the social changes of the Halmahera community in Andaru Intan's 33 Senja di Halmahera novel, and 3) to describe the social values of the Halmahera community in Andaru Intan’s 33 Senja di Halmahera novel. The method used in this study is a qualitative method with a descriptive approach. The analysis was carried out by reading the novel 33 Senja di Halmahera and then analyzing the novel by noting every quote related to the social aspects of the Halmahera community. The results of the research in this study are 1) describing the economic situation in Halmahera which still requires assistance from various parties and the results of the community's main search, 2) describing the social changes that occurred after horizontal conflict, and 3) describing the social values of the Halmahera community in the form of ethics, social status, and religion. This novel can be clearly described about the economy, social change, and the social values of the Halmahera community.Keywords: portrait of life, social aspect, cultural aspect, novel 33 Senja di Halmahera